Steganografi Video Digital dengan Algoritma LSB (Least Significant Bit) dan Rijndael - Imam Riadi; Sunardi; Dwi Aryanto (Journal of Innovation Information Technology and Application (JINITA), 2020)
Steganography is the science and art of hiding information so that confidential information cannot be known by others, except the sender and receiver. This research is designed to create a steganography system on video with mp4 format. The message is inserted in one of the video frames, first encrypted with the Rijndael algorithm. The method of inserting messages in the video frame is the Least Significant Bit (LSB) method. Extraction of frames on video using ffmpeg software. Qualitative testing used to identify changes in video frames with human senses. Quantitative testing was carried out by testing six videos with different resolutions, while there were five inserted messages with varying Byte lengths. The frame that has been inserted with a message is measured for noise with the Peak Signal to Noise Ratio (PNSR). The test results show that the LSB method cannot be used for message insertion whose Byte size is greater than the capacity of the cover video. There is a change in image quality if the size of the inserted message bytes is getting bigger.